Research gaps identified during systematic reviews of clinical trials: glass-ionomer cements - Mickenautsch Steffen (BMC, 2012)
Abstract Background To report the results of an audit concerning research gaps in clinical trials that were accepted for appraisal in authored and published systematic reviews regarding the application of glass-ionomer cements (GIC) in dental practice Methods Information concerning research gaps in trial precision was extracted, following a framework that included classification of the research gap reasons: 'imprecision of information (results)', 'biased information', 'inconsistency or unknown consistency' and 'not the right information', as well as research gap characterization using PICOS elements: population (P), intervention (I), comparison (C), outcomes (O) and setting (S). Internal trial validity assessment was based on the understanding that successful control for systematic error cannot be assured on the basis of inclusion of adequate methods alone, but also requires empirical evidence about whether such attempt was successful. Results A comprehensive and interconnected coverage of GIC-related clinical topics was established. The most common reasons found for gaps in trial precision were lack of sufficient trials and lack of sufficient large sample size. Only a few research gaps were ascribed to 'Lack of information' caused by focus on mainly surrogate trial outcomes. According to the chosen assessment criteria, a lack of adequate randomisation, allocation concealment and blinding/masking in trials covering all reviewed GIC topics was noted (selection- and detection/performance bias risk). Trial results appear to be less affected by loss-to-follow-up (attrition bias risk). Conclusion This audit represents an adjunct of the systematic review articles it has covered. Its results do not change the systematic review's conclusions but highlight existing research gaps concerning the precision and internal validity of reviewed trials in detail. These gaps should be addressed in future GIC-related clinical research.